Digital Transformation of Information Systems and Information Technology in Procurement and Purchasing - Netsawang, Wanwisa (Arts of Management Journal, 2026)
This academic article aimed to present the digital transformation model of information systems and information technology in procurement and purchasing, analyzing strategic frameworks that integrate various technologies to enhance supply chain capabilities. This study employed a Systematic Literature Review (SLR) of national and international academic databases (including TCI, Scopus, and Google Scholar) from 2018 to 2025 based on clearly defined selection criteria. The study revealed that six foundational technologies are essential for modern procurement and purchasing: Electronic Data Interchange (EDI), Barcode technology (EAN-13 standard), Radio Frequency Identification (RFID), Enterprise Resource Planning (ERP), Warehouse Management System (WMS), and Microsoft Excel. This article proposes a consolidated “Digital Procurement Transformation Model” that structures these technologies into three maturity stages: Digitization, Integration, and Intelligent Transformation. It further discusses the integration of contemporary technologies, such as Artificial Intelligence (AI) and Blockchain, to bridge existing gaps in classical literature.